Methylsulfonylmethane Increases the Alveolar Bone Density of Mandibles in Aging Female Mice - Aljohani, Hanan; Senbanjo, Linda T.; Al Qranei, Mohammed; Stains, Joseph P.; Chellaiah, Meenakshi A. (Frontiers in Physiology, 2021)
Methylsulfonylmethane (MSM) is a naturally occurring anti-inflammatory compound that effectively treats multiple degenerative diseases such as osteoarthritis and acute pancreatitis. Our previous studies have demonstrated the ability of MSM to differentiate stem cells from human exfoliated deciduous teeth into osteoblast-like cells. This study examined the systemic effect of MSM in 36-week-old aging C57BL/6 female mice in vivo by injecting MSM for 13 weeks. Serum analyses showed an increase in expression levels of bone formation markers (osteocalcin and P1NP) and a reduction in bone resorption markers (TRAP, CTX-I) in MSM-injected animals. We found that MSM exerts a different impact on long bones, i.e., tibia, femur, and flat bones, i.e., mandible. Micro-computed tomographic images demonstrated an increase in trabecular bone density in mandibles; the trabecular bone density tended to be higher in the femur, although the increase was not significantly different between the MSM- and PBS-injected mice. Histomorphometric analysis of the tibia revealed a noticeable difference in the newly formed bone at the metaphyseal plate with an increase in the osteoblasts observed. In mandibles, an increase in bone density with a corresponding decrease in the marrow cavity was observed in the MSM-injected mice. Furthermore, immunohistochemical analyses of the mandibles for the osteoblast-specific marker—osteocalcin (OCN) and the mesenchymal stem cell-specific marker—CD105 showed a significant increase and decrease in OCN and CD105 positive cells, respectively. In conclusion, our study has demonstrated the ability of MSM to induce osteoblast formation and function in vivo, resulting in increased bone formation in the mandible and possibly in long bones. Hence, the application of MSM and stem cells of interest may be the right combination to use in alveolar bone regeneration under periodontal or other related diseases that demonstrate bone loss.